Leukocyte-and platelet-rich fibrin does not provide any additional benefit for tooth extraction in head and neck cancer patients post-radiotherapy: A randomized clinical trial (2020)
BACKGROUND:One of the most important complications of radiotherapy (RT) for head and neck cancer (HNC) is osteoradionecrosis (ORN) of the jaws, arising mainly from tooth extractions. Thus, the present study aimed to evaluate the efficacy of leukocyte- and platelet-rich fibrin (L-PRF) in preventing ORN following tooth extraction in post-irradiated HNC patients, as well as other postoperative complications. MATERIAL AND METHODS:23 patients previously submitted to conventionally fractionated 3D-conformational RT for HNC underwent atraumatic tooth extractions with perioperative antibiotic therapy. Besides, they were randomly assigned to receive L-PRF clots to fill and cover the extraction sockets (n=11, Test Group) or not (n=12, Control Group). A visual analog scale was used to quantify postoperative pain on the 3rd and 7th days. For ORN diagnosis, patients were clinically assessed for up to 180 days. Other postoperative complications (edema, alveolitis, suture dehiscence, continuous bleeding, and oroantral communication) were also evaluated within this period. RESULTS:No case of ORN or another surgical complication was observed and there were no differences in the postoperative pain scores between the groups on the 3rd and 7th days. CONCLUSIONS:L-PRF did not seem to provide any additional benefits than those achieved by the combination of the surgical and drug protocols used for tooth extractions in the post-irradiated HNC patients.